2022
DOI: 10.1002/cncr.34410
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of use and outcomes of peripherally inserted central catheters in hospitalized patients with solid tumors: A multicenter study

Abstract: BACKGROUND:The risk of peripherally inserted central catheter (PICC)-related complications in patients hospitalized with solid tumors remains unclear. Existing studies are limited by single-center, outpatient designs and include heterogenous patients. METHODS: A retrospective cohort study was designed and included adult patients with solid organ cancers who were admitted to a general medicine ward or intensive care unit and received a PICC. Data were collected from November 2013 to December 2019 at 50 Michigan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This study has limitations. First, its single-center design could limit the extrapolation of the results, as PICC-related complication rates vary between hospitals [ 15 ]. However, our cohort included a large number of patients from four different oncology departments and one hematology department, representing a mix of different practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has limitations. First, its single-center design could limit the extrapolation of the results, as PICC-related complication rates vary between hospitals [ 15 ]. However, our cohort included a large number of patients from four different oncology departments and one hematology department, representing a mix of different practices.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients treated with chemotherapy, the use of PICCs has increased dramatically [ 11 ] but studies provide conflicting data regarding the risk of CVC-related complications, with some reporting that implantable port catheters are safer [ 12 ], others that PICCs are safer [ 13 ], and finally, some authors report that both devices are equivalent [ 14 ]. Moreover, the risk of PICC-related complications in cancer patients compared with noncancer patients remains poorly assessed [ 15 ]. The complication rate appears to be higher in cancer patients than in noncancer patients, especially with regard to the PICC thrombosis rate [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tunneled venous catheters with external line access, such as Broviacs ® and Hickmans ® , are functional line options, but in clinical practice are more often placed for allogeneic hematopoietic stem cell transplantation (HSCT) and are not usually present in patients receiving upfront leukemia therapy or CAR T cell therapy. While PICC lines can be placed for the administration of CAR T cell therapy, PICCs have demonstrated significant risk of complications, including central-line associated infections, catheter occlusion, and thrombosis (deep vein thrombosis and pulmonary embolism) (9).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that a dual immune checkpoint inhibitors (ICI) regimen has shown even greater benefits for dMMR/MSI-H metastatic colorectal cancer ( 7 ). Chemotherapy combined with targeted drugs is the first-line standard treatment for advanced colorectal cancer, but there is still a risk of progression after drug resistance, and adverse events in cancer patients are obvious ( 8 , 9 ). Randomized controlled trials (RCT) have shown that patients receiving FOLFOX6 plus bevacizumab as first-line treatment for RAS mutant colorectal cancer had objective response rates of 54.5%, median progression-free survival 9.5 months, and median overall survival of 25.7 months; the incidences of proteinuria and hypertension were 9.9% and 8.3%, respectively ( 10 ).…”
Section: Introductionmentioning
confidence: 99%